Framing Air Pollution: Analyzing Coverage, Themes, and Policy Discourse in the New York Times - Berdimuratov, Aydogdy (Department of Communications, Universitas Islam Indonesia, 2025)
This study investigates how The New York Times frames air pollution, a pressing environmental challenge with far-reaching implications. Employing content analysis guided by agenda-setting theory, it examines 53 articles published between July 2024 and September 2024 to understand coverage frequency, thematic focus, framing strategies, policy discussions, and geographic emphasis. Findings reveal a dominance of crisis dreams and health-focused themes, with limited attention to policy solutions and grassroots perspectives. National and international narratives, particularly European ones, overshadow local issues, reflecting biases and coverage. Despite highlighting urgency, the lack of solution-oriented reporting risks fostering public helplessness. The study underscores the need for balanced environmental communication, integrating actionable narratives and diverse stakeholder voices to enhance public engagement and policy advocacy. Limitations, including reliance on a single publication and manual coding, suggest avenues for future research to explore broader media dynamics and diverse environmental topics. This analysis contributes to understanding the media's role in shaping discourse on environmental governance.